TANGGUNG JAWAB PARA PIHAK DALAM PRA KONTRAK MENURUT HUKUM KONTRAK DI INDONESIA - Carlisa Amadea Yulivianti (2021)
In essence, the emergence of a contract begins with a difference in the interests of the parties. The contract formation process includes three stages, namely pre-contract, contract execution, and post-contract. In developed countries that adhere to a civil law system, such as France, the Netherlands, and Germany, courts apply the principle of good faith not only in the signing and execution stages of the contract but also in the pre-contract stage, so that the non-fulfillment of the principle of good faith in the pre-contract can be prosecuted by getting compensation. This study raises the problem of how the position and function of pre-contracts in Indonesian contract law (agreements) and responsibility of the parties in the pre-contract stage. This study uses normative research method using literature study with comparative, conceptual and case approach. The results of the study indicate that there is no regulation of the contract formation process in Indonesian contract law resulting in problems at the pre-contract stage. The existence of pre-contract problems in Indonesia is evidence that the principle of good faith is not implemented in the pre-contract stage. The importance to build of pre-contract regulations in contract law in Indonesia, to provide legal protection for parties who suffer losses as a result of promises made at the pre-contract stage.